Severe Diarrhea outbreak in Islamabad - Asim Mehmood, Jahanzeb Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Diarrhea caused by enteric infections is one of leading causes of morbidity and mortality across the world. Several bacterial pathogens are known to cause diarrhea including Vibrio cholera, Clostridium difficile, Shigella and selected strains of Escherichia coli (E. coli). Clinical features of acute infectious diarrhea include abdominal cramps, nausea, fever, vomiting and blood and mucus in the stool. Islamabad, the capital territory of Pakistan has recently come into a wrap of an outbreak of infectious diarrhea which is affecting the masses and is still continuing to do so. Islamabad health care system came collapsing during the last major outbreak of Corona Virus and showed areas that needed improving, thus this endemic should be taken seriously while it is in its bud. This letter addresses the latest outburst of diarrhea that demands an urgent and immediate attention. Letter also provides with precautionary measures and management techniques that should be picked up the relevant authorities and public.